Authoritarian liberalism, ordoliberal rationality and the European integration project - Popov, Maksim Evgen'evič (Teorija in praksa, 2023)
The author assesses the relevance and analytical significance of authoritarian liberalism and interprets it as one of the modern conceptual models of ordoliberalism and European integration. The basic concepts of authoritarian liberalism and ordoliberalism emphasise the political and ideological connection between the authoritarianism of the strong state and the economic liberalism of market rationality. As a flexible market-oriented form of authoritarian liberalism, ordoliberalism means a rational strategy for maintaining and promoting the European integration project towards which the market economy and the technocratic elite are moving to contain crises. Due to the presence of the values of political liberalism, pluralism and the rule of law, authoritarianism in this structure is not repressive or monocentric, but subject to democratic criticism in relation to the supranational regulation of European integration.
Keywords: authoritarian liberalism; Avtoritarizem; avtoritarni liberalizem; democracy; demokracija; eurocrisis; European integration; evrokriza; evropska integracija; Evropska unija; Liberalizem; market capitalism; ordoliberalism; ordoliberalizem; tržni kapitalizem